(untitled) (Contemporary Mathematics, 2024)
In the present study, we provide an efficient numerical approach for solving singularly perturbed nonlinear ordinary differential equations with two integral boundary conditions. We specifically propose a numerical approach for the solution of a nonlinear singular perturbed problem with integral boundary conditions. To solve the nonlinear singularly perturbed issue, we also apply finite difference methods. It explores how a specific derivative and a problemsolving approach behave. Finally, a numerical technique that employs a finite difference scheme is built using a nonuniform mesh.